Of manners and murder - Hastings, Anastasia (Hastings, Anastasia. Dear Miss Hermione mystery, 2023)
"Of Manners and Murder is the first in the delightful new Dear Miss Hermione mystery series from Anastasia Hastings. 1885: London, England. When Violet's Aunt Adelia decides to abscond with her newest paramour, she leaves behind her role as the most popular Agony Aunt in London, "Miss Hermione," in Violet's hands. And of course, the first letter Violet receives is full, not of prissy pondering, but of portent. Ivy Armstrong is in need of help and fears for her life. But when Violet visits the village where the letters were posted, she find that Ivy is already dead. She'll quickly discover that when you represent the best-loved Agony Aunt in Britain, both marauding husbands and murder are par for the course"--